1967
DOI: 10.1677/joe.0.0390189
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen Synthesis in Vitro by Ovaries From Rats in Different Phases of the Oestrous Cycle

Abstract: Ovaries taken from rats in oestrus converted more [4-14C]testosterone to [14C]oestrone and [14C]oestradiol-17\g=b\ than did ovaries taken at dioestrus. Little difference was found in the conversion of [4-14C]androst-4-ene-3,17\x=req-\ dione to [14C]oestrone by either type of tissue.These results suggest that testosterone, rather than androstenedione, is an endogenous oestrogen precursor in the rat.The ability of the rat ovary to produce oestrogen in vitro from C-19 steroids during dioestrus is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Estrogen synthesis in the Graafian folli- Endo • 1975 Vol 96 • No 3 cle has been demonstrated in several species, such as cow (19), pig (20), rabbit (21,22,23), sheep (24), and human (25,26). Although it is generally theorized that the theca are the estrogen-producing cells of the Graafian follicle (1,4,14) there has been experimental evidence that the granulosa cells contribute to estrogen production.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen synthesis in the Graafian folli- Endo • 1975 Vol 96 • No 3 cle has been demonstrated in several species, such as cow (19), pig (20), rabbit (21,22,23), sheep (24), and human (25,26). Although it is generally theorized that the theca are the estrogen-producing cells of the Graafian follicle (1,4,14) there has been experimental evidence that the granulosa cells contribute to estrogen production.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on the direct stimulatory effect of LH on ovarian aromatizing enzymes have not been done by others. However, numerous indirect experiments indicate that this site of action exists (Rabinowitz & Dowben, 1955;Cedard, Varangot & Yanotti, 1964;Gospodarowicz, 1964;Oakey & Stitch, 1967;Kalvert & Bloch, 1968;Villee, Channing, Sulivich & Eckstein, 1969). The placental studies of Cedard, Alsat, Ego & Varangot (1968) clearly demonstrated that LH in vitro exerts a stimulatory action on androgen aromatization.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rate of synthesis of radioactive oestrone and oestradiol-17/? from labelled 4-androstene-3,17-dione was found to be independent of the oestrous state of the donor animals (Oakey & Stitch, 1967). It may be con¬ cluded from comparison of our results with the concentration of oestrogens in ovarian vein and peripheral plasma (Yoshinaga et al 1969;Brown-Grant et al 1970 In the experiments aimed to detect an effect of added gonadotrophin on [14C]-oestrogen synthesis, the particular experimental design used was selected to minimize problems associated with the variability in samples of ovarian tissue.…”
Section: Methodsmentioning
confidence: 70%
“…Previous studies from this labora¬ tory have identified [14C]oestrone and [14C]oestradiol-17/? as metabolites of [14C]-testosterone incubated with rat ovaries in vitro, following similar purification pro¬ cedures (Stitch, Oakey & Eccles, 1963;Oakey & Stitch, 1967).…”
Section: Methodsmentioning
confidence: 99%